Stranger Things: Science Camp #3 #3 / Science camp. - Houser, Jody; Salazar, Edgar, 1973-; Champagne, Keith; Louise, Marissa; Piekos, Nate (Minneapolis, Minnesota : Spotlight, 2022)
While Dustin continues to prove his mettle as a Dungeons and Dragons DM to prove a point to new-found camp bullies, the counselors of Camp Know Where have been disappearing one by one. When Suzie and Dustin discover the older teenagers running the camp are the targets of a sinister plot, they decide to solve the mystery on their own.
Keywords: Camps -- Comic books, strips, etc; Disappearances (Parapsychology) -- Comic books, strips, etc; Monsters -- Comic books, strips, etc; Disappearances (Parapsychology) -- Fiction; Monsters -- Fiction; Camps -- Fiction; Cartoons and comics; Horror comics; Graphic novels